ORALLY LACTATE CALCIUM AND SWIMMING DECREASE OSTEOCLAST AND INCREASE OSTEOBLAST IN RADIAL PERIMENOPAUSAL MICE (MUS MUSCULUS) BONE - **, Muliani (Medicina, 2012)
Calcium and moderate intensity swimming exercise can increase bone density. The aim of this research is to see the effect of orally calcium consumption and swimming activity to decrease osteoclast and increase osteoblast in radial perimenopausal mice (Mus musculus) bone. Pretest and pos#est control group design was used in this research. Research subject used 15-16 aged mice (Mus musculus) which divided into 4 groups (each group consisted of 13 mice), that was control, lactate calcium, swimming and lactate calcium and swimming. Treatment was given 90 days. This study showed a significant difference of the mean of the pos#est osteoblast between control and experimental groups (P<0.05). There was no significant difference between lactate calcium and swimming groups (P>0.05). Enhancement of osteoblast mean in combination group was greater than the other experimental groups. There was a significant difference of the mean of the pos#est  osteoclast between control and experimental groups (P<0.05), without significant difference between lactate calcium,   swimming groups and combination of lactate calcium and swimming group (P>0.05).  Conclusion: either lactate calcium or swimming decreases osteoclast and increases osteoblast of the mice but the osteoblast enhancement will be bigger when they are given together at once